Development : A Study of the Indian Manufacturing Industry - Hulten, Charles; Bennathan, Esra; Srinivasan, Sylaja (Oxford University Press on behalf of the World Bank, 2013)
If infrastructure tends to generate spillover externalities, as has been the assumption in much of the development literature, one may reasonably look for evidence of such indirect effects in the accounts of manufacturing industries. Empirical support for this assumption has so far been ambiguous. This analysis of Indian data, however, reveals substantial externality effects from the states' infrastructure to manufacturing productivity. The analysis separates the direct effects of roads and electricity, as mediated by the infrastructure services purchased by manufacturing industries along with other intermediate inputs, from the indirect effects, as measured by the impact of infrastructure capacity on the Solow productivity residual. In the 20 years from 1972 to 1992, growth of road and electricity-generating capacity seems to have accounted for nearly half the growth of the productivity residual of India's registered manufacturing.